Prevalence of malnutrition in hospitalized 6-24 months old infants in Kerman university hospital NO.1 - A.A Vahidi; M.H Torabinejhad; A Ahmadi; F GHazanfaripour (Journal of Kerman University of Medical Sciences, 2001)
malnutrition is one of the important health problems in developing countries.it may have undesireable effects on mental and physical state of children and is an underlying factor for many infections.the aim of this study was to find out the prevalence of malnutrition in 6-24 month old in fanst in the pediatric ward of university hospital NO.1  in Kerman.for this purpose , the weight and height of 560 infants aged 6-24 months who were hospitalized during 1 year were measured and compared with the weight  and height of 496 peer children who reffered to the health centers for monthly chechups.the nutritional status of both group was evaluated according to the weight for age(Gomez).weight for hright (Waterlow) and height  for age(Waterlow) methods.43.5% of hospitalized infants were girls and 56.5% were boys.in the control group, the percentage of girls and boys were 39.5% and 60.5 % repectively.According to the weight for age(Gomez), the weight for height (Waterlow), and the height for age methode, the prevalence of malnutrition in hospitalized infants and control group were 76.2% and 60.5% (p<0.0001), 74.7% and 57.5%(p<0.0001) and 40.7% and 41%(p>0.23),respectively.according to the waterlow method,there was a statistically significant differecce(p<0.05) in malnutrition rate between boys(81.2%) and girls(65.5%) in hospitalized infants .the mothers, educational level,birth order,and parents, occupation had a significant role in the prevalence of malnutrition,but there was no significant difference in malnutrirtion of breast feeding and formula-feeding infanst.the  majority of malnutrirtion cases were seen in infants who were suffering from cardiac,respiratory and diarrheal disorders or urinary tract infection.with respect to the fact that malnutrirtion is the predisposing factors for many infections and increases the chance for hospitalization,it is proposed that all hospitalized infants should also be evaluated and treated for malnutrition.therefore,in order to decreas the rate of malnutrition, the physicians and health care workers must acquire more experience in prevention,diagnosis, and treatment of malnutrition.the importance of proper feeding must also be explained to the families.